A retrospective vision of the first 14 years on superconducting ceramic oxide materials research in the UNMSM - González, J. C. (2011)
In April 2011 took place in the world’s first 100 years of the discovery of superconductivity. Super- conductivity has been the focus of fundamental solid state physics, applied sciences and engineering. Today it is possible to use superconducting materials in a first generation of superconducting devices and in the near future in magnetically levitated trains, superconducting wires, quantum computers, new generation mobile phones, new MRI equipment, etc. The group of superconducting ceramic oxide materials belonging to the UNMSM have studied with great interest the YBa2 Cu3 O7 superconducting material, investigating the incorporation of different cations and anions in different atomic sites in the YBa2 Cu3 O7 structure, as well as derivatives of this structure, to understand their structural, chemical and superconducting properties, then proposing new superconducting compounds. We celebrate the first century of the discovery of superconductivity by a retrospective view of our results in the first 14 years of research.